LGG-28. NEUROCOGNITIVE SEQUELAE IN PEDIATRIC LOW GRADE GLIOMA PATIENTS UNDER OBSERVATION - NEUROPSYCHOLOGICAL RESULTS FROM THE SIOP-LGG-2004 STUDY & LGG-REGISTER. Issue 2 (22nd June 2018) - Traunwieser, Thomas; Kandels, Daniela; Gnekow, Astrid
Abstract: OBJECTIVE: Neuropsychological late-effects for pediatric low-grade-glioma (LGG) patients under observation following complete or subtotal tumor resection (CR), or biopsy or radiological diagnosis only, are poorly defined. We report results of the German "neuropsychological basic diagnostic" tool (NBD) in LGG-patients without neurofibromatosis NF1 under observation from the German and Swiss SIOP-LGG-2004 & LGG-Register cohort. PATIENTS & METHODS: LGG-patients ≥4 years of age from 32 oncology centers were examined 2 (T1) and 5 years (T2) after diagnosis with the NBD measuring primary cognitive abilities with age-appropriate tests: fluid intelligence (FI), verbal short-term-memory (SM), visual-motoric integration (VMI), vocabulary (VB), fine-motor skills (FM) and processing speed (PS). 42 CR-patients were assessed at T1 and 52 at T2; tumor sites were infratentorial only. 20 patients observed following biopsy or radiological diagnosis were assessed at T1 and 14 at T2. Tumor sites were supratentorial-hemispheric (18%), supratentorial-midline (62%), infratentorial (20%). Because of extended overall neurocognitive impairment in previous analysis, NF1-patients were excluded. RESULTS: At T1, CR-patients displayed statistically noticeable deficits compared to expected population score in VMI, FM and PS (p<.001-.004; r=.47-.88). This was unchanged in the same dimensions at T2 (p<.001-.007; r=.45-.82). Biopsy and no-treatment patients showed statistically noticeable impairments at T1 in FM and PS (p<.001-.013; r=.65-.84), and additionally in VMI at T2 (p=.002-.041; r=.59-.90). CONCLUSION: Previous reports implied neuropsychological sequelae for the entire LGG-cohort "under observation". This more detailed analysis underscores, that deficits occur in all subgroups, and that impairments, especially in motoric and in information processing tasks, of mostly high effect sizes even persist over time.